2015
DOI: 10.1108/ss-01-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain integration with BIM: a graph-based model

Abstract: Purpose – The purpose of this paper is to propose a methodology to integrate the construction Supply Chain (SC) through the application of Building Information Modeling (BIM) and Supply Chain Management (SCM). It features a renovation case as a proof-of-concept. Design/methodology/approach – After analyzing the relevant gaps in the literature, the research followed a modeling approach. The proposed model merged product-, process- and org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…From the findings, higher fees charged did not have a significant effect on the delivery performance of organisations. Furthermore, aligns with the view that BIM process quality is regarded as superior to price considerations in the selection of organisations to be part of the supply chain of BIM projects in Netherlands (Papadonikolaki et al, 2015).…”
Section: Discussion Of Findingssupporting
confidence: 65%
“…From the findings, higher fees charged did not have a significant effect on the delivery performance of organisations. Furthermore, aligns with the view that BIM process quality is regarded as superior to price considerations in the selection of organisations to be part of the supply chain of BIM projects in Netherlands (Papadonikolaki et al, 2015).…”
Section: Discussion Of Findingssupporting
confidence: 65%
“…Further, issues the level, the way of interaction and cooperation's of supply chain firms. Papadonikolaki et al (2015) identified that interactions of the supply chain actors and supply chain integration lies in organizational structures, roles, and interactions and integrate the industry. Some researches focused on the manufacturing process and product types.…”
Section: Methods and Strategies Of Supply Chain Integrationmentioning
confidence: 99%
“…However, the performance of the firm measured using cost, and resource utilization as quantitatively, whereas quality, flexibility, visibility, trust and innovativeness were evaluated firms as qualitative manner (Chan, 2003). Also, from this analysis found that the performance measures were used and practices based on the goals of the supply chain (Kurien & Qureshi, 2011;Otto & Kotzab, 2003), and the geographical separation of the firm and the development of the countries (Fasika Bete Georgise et al, 2013) were considered. On the other side, performance measurement has great power on measuring the traditional and non-traditional performance of the firms (Kazemkhanlou & Ahadi, 2014).…”
Section: Supply Chain Performance Measurementsmentioning
confidence: 99%
“…Building information modelling (BIM) has been acknowledged as a new cutting-edge innovation in the global construction industry. This attention stems from ample evidence that BIM has affirmed its capability to illuminate current issues in the construction industry (Succar and Kassem, 2015;Rostami et al, 2015;Wang and Chong, 2015;Papadonikolaki et al, 2015). As the global BIM market evolves, BIM has started to be embraced by the global construction industry, with the capability of attaining better construction productivity (Shan et al, 2012;Poirier et al, 2015;Sacks and Barak, 2008).…”
Section: Introductionmentioning
confidence: 99%